Incidence of the quarantine due to covid-19, in the air quality (NO2) of the city of Lima - Chávez Flores, Erick (2020)
The objective of the research is to evaluate the incidence of quarantine due to covid-19, in the variation of the concentration of NO2 (nitrogen dioxide) in the months of March, April and May of the year 2019 and 2020, in the city of Lima . It was carried out under a quantitative approach and its design was non-experimental. The environmental bulletins of the National Institute of Statistics and Informatics (INEI) for 2019 and 2020 (March, April and May) were used. An inferential analysis was applied using the Mann-Whitney U test using the SPSS 25 program. The Mann-Whitney U test showed that the application of compulsory social isolation (quarantine) presented a significant difference (U = 28845.50, p <0.05 ) in NO2 concentration (µg / m3) for the year 2020 compared to 2019 (March, April and May). Likewise, during the months of March 2019-2020 (U = 3511, p <0.05), April 2019-2020 (U = 2758, p <0.05) and May 2019-2020 (U = 2422.5, p <0.05) showed significant differences. It was concluded that the mandatory social isolation (quarantine) due to covid-19 generated a positive impact on air quality in the city of Lima; decreasing the concentration of NO2 (µg / m3) in the months of March, April and May for the year 2020, due to the low vehicular circulation of public and private transport.